Pengaruh Penggunaan Media Pembelajaran Interaktif Berbasis Multimedia Virtual Lab PhEt Terhadap Hasil Belajar Kimia Materi Asam Basa - Aqza, Bella Hasbi; Haris, Mukhtar; Supriadi (FKIP University of Mataram, 2024)
The purpose of this study is to determine how the utilization of PhET multimedia virtual laboratory in interactive teaching materials impacts the acquisition of acid-base chemistry knowledge among grade XI students. This research was conducted through a pre-experimental design consisting of pre-test and post-test one group measurements. All students of class XI MIPA SMAN 1 Alas Sumbawa Besar constituted the population, while purposive sampling was conducted on class XI MIPA 3 consisting of 34 four students. Data collection instruments such as questions during the pre-test and post-test as well as survey sheets were valid and reliable for the purpose of data assessment. Both multiple choice questions and description questions have a high level of reliability, with values of 0.65 and 0.63 respectively. In addition, the average value of the Aiken V index for validity was found to be at the valid category level of 0.66. The questionnaire instrument used has a high level of reliability and validity with a value of 0.77 and high validity with the average value of the Aiken V index which is in the very valid category range with a value of 0.84. Data analysis techniques such as the N-gain test, normality test, and t-test were used to measure student learning outcomes, while reactions were assessed using the student interest test and resulted in an overall average N-gain value equivalent to a higher value scale. The pre-test significance (sig) value of 0.621 > 0.05 and the post-test value of 0.063 > 0.05 indicated that the pre-test and post-test data values were normally distributed, in accordance with the normality test results. The t-test resulted in a significance level of 0.000 < 0.05 (2-tailed). On the other hand, 74% of students' responses to the use of the materials fell into the interested group. The research findings show that the interest and learning outcomes of chemistry class XI IPA students of SMAN 1 Alas Sumbawa Besar are positively influenced by interactive learning materials based on virtual multimedia PhET lab on acid-base materials.